The contemporary issues on fatwa management in a secular state: the Philippine experience - Tagaranao, Mariam Saidona; Gamon, Alizaman Dumangcag; Wahyono, Zubaidi (USIM Press, 2020)
Fatwa is an authoritative source of rulings rendered by the learned Muslim scholars. It has an important role in answering questions and inquiries related to the Muslim daily lives to avoid from falling farther from an un-Islamic way of life. The Philippine laws recognized the application of fatwa under the provisions of the Code of Muslim Personal Laws and the Organic Act for Muslim autonomous regions in Mindanao on important current issues where Islamic jurisprudence is unclear. This paper will address some legal pronouncement on various contemporary issues related to health, marriage, terrorism and others. The study identifies the mechanism and method used in managing and disseminating fatwa in a secular state like Philippines. It also analyzes its position in the Shariah courts, particularly on the availability of fatwa rulings on relevant cases. Library research has been used in writing this research. Proofs of a given fatwa is based on the following sources: the Qur’an, the Sunnah, the Ijma, the Qiyas, the recognized opinions of the mujtahiden and other subsidiary legal principles. Selected fatwa issued by the muftis’ and ulama from other regions will be discussed including the several shortcomings made by the mufti on fatwa management. Thereafter, the conclusion summarizes the important significance of fatwa as a reliable valid legal source of Islamic rulings in the Shariah courts. Recommendations and suggestions have been provided on how to give an important position to the fatwa in bridging the gap between the needs of the Muslims and their sustainable co-existence in a wider Filipino-Muslim community. Keywords: Fatwa management, Regional Dar-al Ifta, Shariah courts, Muslim Code